The challenge of the suburban comfort zone and the Durbanites' failure to explore their city - Vandersteen, Jasmin (The IIE, 2018)
This small-scale, qualitative study sought to understand why the Durban creative class, aged 18-23, who dwell in suburban areas and fall within LSM 8-10, do not explore their city passed their suburban comfort zone and therefore do not engage with the hidden gems that make their city unique. The study consulted relevant literature on the topic and collected primary data using a sample of sixteen participants who took part in two focus groups and four personal semi-structured interviews. The research findings are not generalisable to the larger population as the aim of this qualitative study was to gain a deeper understanding of the perceptions of the creative class. Research findings uncovered various hindrances to the creative class’ exploration such as the convenience and familiarity of suburbia. It also highlighted particular interests, such as creative experiences, that could motivate the creative class to explore despite these hindrances. In addition to this, the study identified irrelevant and preferred ways of making the creative class aware of their city’s hidden gems. The insights uncovered through this study provide an understanding of how to increase the movement, happiness and sociability of the creative class, which in turn can create a positive perception of Durban, retain occupants and lead to the increase of small business and city-wide revenue.
Keywords: City attractions; Urban living; Local attractions; Tourist attractions; Tourism; Suburbia; Suburbs; City life